2018
DOI: 10.1002/acp.3425
|View full text |Cite
|
Sign up to set email alerts
|

Within a hair's breadth of buying the product: The impact of tangible and intangible bodily cues of contamination: The role of disgust and mental imagery

Abstract: In most retail environments, customers can handle products. However, the downside of this freedom to touch products is product contamination. The objectives of this paper are threefold: (a) to examine the effects of contamination cues (tangible vs. intangible) on consumer responses; (b) to show the mediating role of contamination, disgust, and mental imagery; and (c) to assess the robustness of the results on three product categories for different levels of contact intimacy. Three experimental laboratory studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This finding is consistent with the findings reported in most product literature (e.g., Luangrath et al, 2022; Peck & Shu, 2009). However, this is inconsistent with a few studies that have reported a negative touch effect (e.g., Gérard and Helme‐Guizon 2018) and a few studies that have reported a non‐existent touch effect (Liu et al, 2017; Liu et al, 2022; Peck & Wiggins, 2006). We believe the differences in the effect sizes can explain this inconsistency.…”
Section: Discussionmentioning
confidence: 89%
“…This finding is consistent with the findings reported in most product literature (e.g., Luangrath et al, 2022; Peck & Shu, 2009). However, this is inconsistent with a few studies that have reported a negative touch effect (e.g., Gérard and Helme‐Guizon 2018) and a few studies that have reported a non‐existent touch effect (Liu et al, 2017; Liu et al, 2022; Peck & Wiggins, 2006). We believe the differences in the effect sizes can explain this inconsistency.…”
Section: Discussionmentioning
confidence: 89%